THE BANK OF EMISSION IN THE ECONOMY OF COLONIAL INSTALLATION IN AOF - (:unkn) unknown (My University, 2017)
The bank as a financial institution was an instrument of domination during the colonial period in French West Africa. As such, it played an avant-garde role, capital in the hands of the colonizer to establish its hegemony over the colonized populations of French Black Africa. Thus, this tool served to establish a colonial economic policy based on the subjugation of the peoples of black Africa in general but those of French West Africa in particular.
Keywords: African Research